Milk: A Scientific Model for Diet and Health Research in the 21st Century - German, J. Bruce; Lebrilla, Carlito; Mills, David A. (Frontiers in Nutrition, 2022)
The origin of lactation and the composition, structures and functions of milk’s biopolymers highlight the Darwinian pressure on lactation as a complete, nourishing and protective diet. Lactation under the driving pressure as a sustainable bioreactor selected for biopolymers with diverse functions acting from the mammary gland through the digestive system of the infant. For example, milk is extensively glycosylated and the glycan structures and their functions are now emerging. Milk contains free oligosaccharides; complex polymers of sugars whose stereospecific linkages are not matched by glycosidic enzymes within the mammalian infant gut. These glycan polymers reach the lower intestine undigested. In this microbe-rich environment, bacteria compete to release and ferment the sugars via different hydrolytic strategies. One specific strain of bacteria, Bifidobacteria longum subspecies infantis, is uniquely equipped with a repertoire of genes encoding enzymes capable of taking up, hydrolyzing and metabolizing the complex glycans of human milk. This combination of a distinct food supply and unique genetic capability shapes the composition and metabolic products of the entire microbial community within the lower intestine of breast fed infants. The intestinal microbiome dominated by B. infantis, shields the infant from the growth of gram negative enteropathogens and their endotoxins as a clear health benefit. The world is facing unprecedented challenges to produce a food supply that is both nourishing, safe and sustainable. Scientists need to guide the future of agriculture and food in response to these 21st century challenges. Lactation provides an inspiring model of what that future research strategy could be